TANGGAPAN MASYARAKAT TERHADAP PROGRAM KONVERSI MINYAK TANAH KE LPG (Studi Pada Masyarakat Dusun Ribu-Ribu Kampung Bukit Gemuruh Kecamatan Way Tuba Kabupaten Way Kanan) - Komalasari, Eva; Wirawan, Bintang (SOCIOLOGIE, 2013)
Energy is very important role in public life for energy is essential parameter for development and economic growth. Almost all sectors life ( industry, household appliances transportation, services, and others ) could not be separated from the energy sector. Fuel oil ( bbm ) is one type of energy much used in indonesia especially on the society the lower middle class. This research aims to find out and analyze the response of the community towards conversion program kerosene to LPG. Type in this research is qualitative. Researchers use this method to be able to explain and understand the social situation of community response with the conversion program kerosene to LPG. The results showed that after the conversion of kerosene to LPG, Thousands Village Community-thousands of lost fuel (kerosene or lamp oil) for lighting and fuel kitchen, pengeluran society for the fuel to be increased due to the need to replace oil lamps or kerosene with solar.Keywords: Community responses, conversion program